The research question as the backbone of a scientific project - Huespe, Pablo E. (Revista Argentina de Cirugía, 2026)
When reading a scientific manuscript, it is common to notice a lack of a core idea throughout the work. This means that the manuscript is composed of different parts that have little relationship with each other, creating a true chimera (a mythological animal made up of parts of different animals).